👤

Bonjour,

On considère l’expression E = (x −2)(2x +3)−3(x −2).
1. Développer E.
2. Factoriser E et vérifier que E = 2F, où F = x(x −2).
3. Déterminer tous les nombres x tels que (x −2)(2x +3)−3(x −2) = 0


Merci !


Répondre :

Bonjour,

1. E = (x-2)(2x+3) - 3(x-2)
       = 2x² + 3x - 4x - 6 - 3x + 6
       = 2x² - 4x

2. E = 2x² - 4x = 2(x²-2x) = 2x(x-2) d'où E = 2 (x(x-2)) = 2F

3. (x-2)(2x+3) - 3(x-2) = 0
    2x² - 4x = 0
    2x(x-2) = 0
    donc 2x = 0      ou x-2 = 0
     d'où x = 0        ou x = 2